A production stock model for a distributed deteriorating product with both price and time dependent demand rate under inflation and late paying allowing shortages. (16th September 2020) - Lakshmi, M. Dhivya; Pandian, P.
This paper develops a production stock model for deteriorating products with shortages under the effect of inflation and late paying in which demand is a function of selling price and time. In this article, the model is considered with different deterioration distributions and various time dependent holding costs. This model aids in maximising the total inventory cost by finding the two production periods, the consumption period and the shortage period. Numerical example is presented to understand the developed model. Also, the effect of changes in different parameters on the optimal total cost is graphically presented.